Census-Block-Level Property Risk Estimation Due to Extreme Cold Temperature, Hail, Lightning, and Tornadoes in Louisiana, United States - Mostafiz, Rubayet Bin; Friedland, Carol J.; Rohli, Robert V.; Gall, Melanie; Bushra, Nazla; Gilliland, Joshua M. (Frontiers in Earth Science, 2020)
Rising property losses from natural hazards are typically the result of increased vulnerability, reduced resilience, low hazard mitigation effectiveness, or increased hazard intensities. Such property losses are frequently projected through population and asset growth, without considering changes in hazard frequency or intensity. This research describes a method of estimating risk, defined as projected property loss, anticipated to result from extreme cold temperature, hail, lightning, and tornado hazards through 2050 in the State of Louisiana, U.S.A. Our approach improves previous hazard risk assessments by 1) weighting risk by 2010 and 2050-projected population; 2) adjusting future hazard intensity based on recent climate model projections; and 3) producing results at the “microscale” census block, rather than previous county-wide or larger assessments. On a statewide basis, extreme cold temperature and tornado hazards incur by far the most risk of the four hazards. Extreme cold temperature and hail risk are projected to decrease as temperatures warm, especially in the New Orleans area. The lightning risk, while small, is projected to increase, both on an absolute and per capita basis. The proposed method and Louisiana results are appropriate to assist environmental, community, and emergency management planners in protecting life and property.